2004
DOI: 10.1186/1471-2318-4-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sensory impairment and functional independence among elderly

Abstract: Background: It has been well established that increasing age is associated with decreasing functional ability in older adults. It is important to understand the specific factors that affect instrumental activities of daily living (IADL) and functional independence among older adults with sensory disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 18 publications
5
41
0
Order By: Relevance
“…For example, 73.9 percent of individuals with NSI reported visiting friends, while the numbers were 70.9 percent for those with HI, 66. [48]. The data showed that individuals with DSI reported the most restrictions conducting instrumental activities of daily living (e.g., shopping, housework, personal care, meal preparation), followed by those with VI alone and then those with HI alone.…”
Section: Effectmentioning
confidence: 93%
“…For example, 73.9 percent of individuals with NSI reported visiting friends, while the numbers were 70.9 percent for those with HI, 66. [48]. The data showed that individuals with DSI reported the most restrictions conducting instrumental activities of daily living (e.g., shopping, housework, personal care, meal preparation), followed by those with VI alone and then those with HI alone.…”
Section: Effectmentioning
confidence: 93%
“…Compared with persons who reported no sensory impairment, individuals who reported DSI had approximately 10% lower rates of participation in activities such as visiting friends, telephoning colleagues, going to movies, and attending church. With regard to self-reported health and limitations in activities of daily living (ADL), 16 Studies showing the effect of DSI on functional independence include a study by Raina et al 26 In this study, 16 613 individuals older than 66 years completed the 1991 Health and Activities Limitation Survey in interview format. Data on ability to conduct instrumental ADLs (IADLs) such as shopping, meal preparation, money management, and home maintenance were collected.…”
Section: Effects Of Dsimentioning
confidence: 99%
“…Because the U.S. population of older adults is increasing, the prevalence of low vision conditions is also expected to increase (NEI, n.d.). Studies have indicated that vision loss diminishes personal safety, interferes with engagement in activities of daily living (ADLs), and increases risk of falls and fractures (Cox et al, 2005;Dahlin Ivanhoff, Sonn, Lundgren-Lindquist, Sjörstrand, & Steen, 2000;Dhital, Pey, & Stanford, 2010; National Organization on Disability, 2000; Raina, Wong, & Massfeller, 2004). Despite such concerns, many older adults with low vision have a strong desire to live independently in their own homes (Girdler, Packer, & Boldy, 2008).…”
mentioning
confidence: 99%